Personal finance in your 20s & 30s - Tyson, Eric (Eric Kevin) (--For dummies., 2025)
"When you've officially begun "adulting" and it's time to make big financial decisions, Personal Finance In Your 20s & 30s For Dummies offers step-by-step advice on building a foundation for your financial futures. Bestselling author and money management guru Eric Tyson shares simple guidance on budgeting, investing, insurance, housing, and more, walking you through how to make the decisions you'll need to make to set yourself up for the rest of your life. You'll learn how to manage debt, co-manage your finances with a partner, and distinguish sound information and advice from meaningless noise and trends. The book is a roadmap to financial health and security that's straightforward enough for anyone to follow and applies to people at almost any income level"--